O, Brave New World A Balanchine masterwork - Goldner, Nancy (Dance Books Ltd., Alton,Hampshire (UK), 2002)
A Balanchine masterwork. The great paradox of The Four Temperaments is that despite the pilling and twisting it is one of Balanchine's purest examples of classicism. PALABRAS CLAVE: The Four Temperaments, George Balanchine, Melancholic, Sanguinic, Phlegmatic, Choleric.